BALÍQSHÍLÍQ TARAWÍNDA KÁSIPLIK DIALEKTLIK SÓZLERDIŃ QARAQALPAQ HÁM NEMIS TILLERINDE BERILIWI - Nuranova, S.G. (SCIENCE and SOCIETY, 2023)
In this article, phraseological units related to the term fish in the German and Karakalpak languages were analyzed linguacultural. When writing the article, the information in two languages was analyzed, and the linguistic and cultural connection between them was also considered. When researching fishing terms in the German language, Duden’s dictionary, Karakalpak language sources, D.Nasirov, and O.Dospanov, T.Begjanov, J.Eshbaev, published valuable works, and folklore of Karakalpak, 88-100 volumes, are linguistic, was discussed from linguoculturological points of view.